Nonaqueous electrolyte secondary battery

By using a clip spacer to wind the electrode body in the nonaqueous electrolyte secondary battery and a specific spacer functional layer is provided in the non-opposite part of the negative electrode, the problems of plate deformation and the reduction of primary charge and discharge efficiency caused by the expansion of the electrode body are solved, and more efficient battery performance is achieved.

CN119631221APending Publication Date: 2025-03-14PANASONIC ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380059054.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-24
Filing Date
2023-08-15
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In a nonaqueous electrolyte secondary battery, the electrode body expands during the charge and discharge cycle, causing the plate to deform, and the initial charge and discharge efficiency is reduced.

Method used

An electrode body is formed by winding the positive electrode and the negative electrode through a pair of spacers, and is wound for 1.5 weeks or more in the non-opposed portion of the negative electrode from the winding direction of the electrode body. The functional layer of the spacer includes a heat-resistant layer containing inorganic particles and resin particles dispersed in the heat-resistant layer. The resin particles form a convex portion protruding from the surface of the heat-resistant layer, and the functional layer faces the positive electrode.

Benefits of technology

The deformation of the plate accompanied by the charge and discharge cycle is effectively suppressed, and the initial charge and discharge efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631221A_ABST
    Figure CN119631221A_ABST
Patent Text Reader

Abstract

The nonaqueous electrolyte secondary battery is characterized in that the nonaqueous electrolyte secondary battery has an electrode body (14) in which a positive electrode (11) and a negative electrode (12) are wound with a pair of separators (13) interposed therebetween, the negative electrode (12) has a non-facing portion (12a) that faces the positive electrode (11) without the pair of separators (13) interposed therebetween, and the non-facing portion (12a) is wound at least 1.5 circles from the inner end of the electrode body (14) in the winding direction. At least one of the pair of spacers (13) has a base layer and a functional layer formed on the base layer, the functional layer containing a heat-resistant layer containing inorganic particles and resin particles dispersed in the heat-resistant layer and having an average particle diameter larger than the thickness of the heat-resistant layer. The resin particles form protrusions protruding from the surface of the heat-resistant layer, and the functional layer of at least one of the pair of spacers (13) faces the positive electrode (11).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] In recent years, nonaqueous electrolyte secondary batteries including an electrode body in which a positive electrode and a negative electrode are arranged to face each other with a separator interposed therebetween have been widely used as secondary batteries with high output and high energy density.

[0003] For example, Patent Document 1 discloses a non-aqueous electrolyte secondary battery, characterized in that it comprises an electrode body obtained by winding a negative electrode and a positive electrode with a separator sandwiched therebetween, wherein the negative electrode has a non-opposing portion on the inner circumference of the electrode body that is not opposed to the positive electrode, and the non-opposing portion has at least 2 turns on the inner circumference of the electrode body.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-137946 Summary of the invention

[0007] However, in a non-aqueous electrolyte secondary battery having a wound electrode body, when the electrode body expands with charge and discharge cycles, stress is locally applied to the center of the electrode body, and the electrode plates constituting the electrode body may deform (bend). Such deformation of the electrode plates may be suppressed by arranging the non-opposing portion on the inner end side of the winding direction of the wound electrode body.

[0008] However, the non-aqueous electrolyte is easily retained in the narrow space between the non-opposing portion of the negative electrode on the inner end side of the winding direction of the electrode body and the separator. Therefore, when the battery is charged and discharged, the non-aqueous electrolyte on the non-opposing portion is decomposed, resulting in a problem of reduced initial charge and discharge efficiency of the battery.

[0009] Therefore, an object of the present application is to provide a non-aqueous electrolyte secondary battery capable of suppressing deformation of an electrode plate accompanying a charge and discharge cycle and suppressing a decrease in initial charge and discharge efficiency.

[0010] The non-aqueous electrolyte secondary battery of the present application is characterized in that it has an electrode body obtained by winding a positive electrode and a negative electrode with a pair of separators interposed therebetween, and a non-aqueous electrolyte, the negative electrode having a non-opposing portion which is opposed to the positive electrode with or without the pair of separators interposed therebetween, the non-opposing portion being wound more than 1.5 turns from the inner end of the winding direction of the electrode body, at least any one of the pair of separators having a substrate layer and a functional layer formed on the substrate layer, the functional layer comprising a heat-resistant layer containing inorganic particles and resin particles dispersed in the heat-resistant layer and having an average particle size larger than the thickness of the heat-resistant layer, the resin particles forming a convex portion protruding from the surface of the heat-resistant layer, and the functional layer of at least any one of the pair of separators being opposed to the positive electrode.

[0011] According to the present application, a non-aqueous electrolyte secondary battery can be provided which can suppress deformation of the electrode plate accompanying the charge and discharge cycle and suppress a decrease in the initial charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a schematic cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.

[0013] Figure 2 This is a schematic cross-sectional view of the electrode body as viewed from the winding axis direction.

[0014] Figure 3 It is a schematic cross-sectional view showing an example of a spacer.

[0015] Figure 4 This is a diagram showing the state of the positive electrode, the negative electrode, and the separator by developing the inner end side of the electrode body in the winding direction.

[0016] Figure 5 This is a diagram showing the state of a positive electrode, a negative electrode, and a separator by developing the inner end side in the winding direction of a conventional electrode body.

[0017] Figure 6 It is a diagram for explaining the evaluation method of electrode plate deformation. DETAILED DESCRIPTION

[0018] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present application will be described in detail.

[0019] Figure 1 It is a schematic cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. Figure 1The non-aqueous electrolyte secondary battery 10 shown includes a wound electrode body 14 in which a positive electrode 11 and a negative electrode 12 are wound with a pair of separators 13 interposed therebetween, a non-aqueous electrolyte, insulating plates 18 and 19 disposed above and below the electrode body 14, respectively, and a battery case 15. The battery case 15 is composed of an outer package 16 that accommodates the electrode body 14, the non-aqueous electrolyte, etc., and a sealing body 17 that seals the opening of the outer package 16. The battery case 15 is not limited to a cylindrical or square metal case, and may be, for example, a resin case formed by laminating resin sheets (so-called laminated type) or the like.

[0020] The non-aqueous electrolyte solution includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may also contain a halogen-substituted substance in which at least a portion of the hydrogen in the solvent is replaced by a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6.

[0021] The outer package 16 is, for example, a metal container in a cylindrical shape with a bottom. A gasket 28 is provided between the outer package 16 and the sealing body 17 to ensure the airtightness of the battery interior. The outer package 16 has, for example, a protrusion 22 for supporting the sealing body 17, which is obtained by protruding a part of the side surface inward. The protrusion 22 is preferably formed in an annular shape along the circumferential direction of the outer package 16, and the sealing body 17 is supported by its upper surface.

[0022] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the non-aqueous electrolyte secondary battery 10 rises due to heat caused by an internal short circuit, for example, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.

[0023] Figure 1In the non-aqueous electrolyte secondary battery 10 shown, the positive electrode lead 20 attached to the positive electrode 11 passes through the through hole of the insulating plate 18 and extends to the sealing body 17 side, and the negative electrode lead 21 attached to the negative electrode 12 passes through the outside of the insulating plate 19 and extends to the bottom side of the outer package 16. The positive electrode lead 20 is connected to the lower surface of the filter 23 as the bottom plate of the sealing body 17 by welding or the like, and the cover 27 as the top plate of the sealing body 17 electrically connected to the filter 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer package 16 by welding or the like, and the outer package 16 serves as the negative terminal.

[0024] Figure 2 This is a schematic cross-sectional view of the electrode body as viewed from the winding axis direction. Figure 2 In order to facilitate understanding of the configuration relationship, the negative electrode 12 is represented by a solid line, the positive electrode 11 is represented by a dotted line, and the separator 13 is represented by a single-dot chain line. Figure 2 In the figure, the gap between the positive electrode 11, the negative electrode 12, and the separator 13 is exaggerated. The electrode body 14 is formed by winding the positive electrode 11 and the negative electrode 12 with a pair of separators 13 interposed therebetween. Specifically, the strip-shaped positive electrode 11, the strip-shaped negative electrode 12, and the pair of strip-shaped separators 13 are stacked in the order of one separator 13, the positive electrode 11, the other separator 13, and the negative electrode 12, and the stack is wound into a spiral, thereby manufacturing the electrode body 14. In the electrode body 14, the length direction of each electrode becomes the winding direction, and the width direction of each electrode becomes the winding axis direction.

[0025] like Figure 2 As shown, at the winding start end of the electrode body 14, only the negative electrode 12 of the positive electrode 11 and the negative electrode 12 is arranged. Specifically, the negative electrode 12 has a non-opposing portion 12a that is not opposed to the positive electrode 11 via a pair of separators 13, and the non-opposing portion 12a is separated from the inner end ( Figure 2 The non-opposing portion 12a is wound from point E1) for 1.5 turns. Figure 2 The point E1 shown is a portion extending along the winding direction to the point E2. In addition, the negative electrode 12 has an opposing portion 12b which is wound continuously from the non-opposing portion 12a and is opposed to the positive electrode 11 via a pair of separators 13. It should be noted that Figure 2 In order to make it easier to understand the structure of the pair of separators 13, a gap is provided between the pair of separators 13 adjacent to the non-opposing portion 12a of the negative electrode 12, but in reality, the pair of separators 13 are bonded to each other at this location. The state of the pair of separators 13 at the non-opposing portion 12a of the negative electrode 12 will be described later.

[0026] The non-opposing portion 12a only needs to be wound 1.5 turns or more from the inner end of the winding direction of the electrode body 14, and is preferably wound in the range of 1.5 turns to 3 turns from the inner end of the winding direction of the electrode body 14. Thus, since the stress locally applied to the center of the electrode body 14 along with the charge and discharge of the battery is relieved by the non-opposing portion 12a wound 1.5 turns or more from the inner end of the winding direction of the electrode body 14, deformation (buckling) of the electrode plate can be suppressed.

[0027] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 will be described.

[0028] [positive electrode]

[0029] The positive electrode 11 has a positive electrode collector and a positive electrode mixture layer formed on the surface of the positive electrode collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode collector. The positive electrode collector can use a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film having the metal configured on the surface, etc. The positive electrode mixture layer, for example, includes a positive electrode active material, a binder, a conductive agent, etc. For example, a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc. is applied to the positive electrode collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode collector, thereby making the positive electrode 11.

[0030] Examples of the positive electrode active material contained in the positive electrode mixture layer include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. For example, lithium transition metal oxides are Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li xNiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3) etc. Inorganic particles such as tungsten oxide, aluminum oxide, and compounds containing lanthanide elements may be fixed on the surface of the lithium transition metal oxide particles.

[0031] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon materials, etc. These may be used alone or in combination of two or more.

[0032] Examples of the binder contained in the positive electrode mixture layer include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, polyolefin-based resins, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts, polyvinyl alcohol (PVA), polyethylene oxide (PEO), and the like.

[0033] [negative electrode]

[0034] The negative electrode 12 has a negative electrode collector and a negative electrode mixture layer formed on the surface of the negative electrode collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. The negative electrode collector can use a foil of a metal such as copper or copper alloy that is stable in the potential range of the negative electrode, a film having the metal configured on the surface, etc. The negative electrode mixture layer includes, for example, a negative electrode active material, a binder, etc. The binder can include the same binder as that in the case of the positive electrode 11. For example, a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is applied to the negative electrode collector, and after the coating is dried, it is rolled to form a negative electrode mixture layer on both sides of the negative electrode collector, thereby making the negative electrode 12.

[0035] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and examples thereof include carbon materials and Si-based materials.

[0036] The carbon material may be, for example, a conventionally known carbon material used as a negative electrode active material, such as natural graphite such as flaky graphite, bulk graphite, and earthy graphite, and artificial graphite such as bulk artificial graphite (MAG) and graphitized mesocarbon microbeads (MCMB).

[0037] The Si-based material includes, for example, a lithium ion conductive phase and Si particles dispersed in the lithium ion conductive phase. The lithium ion conductive phase includes, for example, at least one of a silicon oxide phase, a silicate phase, and a carbon phase.

[0038] The silicate phase preferably contains at least one element of the Group 2 elements of the periodic table to which alkali metal elements such as lithium, sodium, potassium, rubidium, cesium, and francium, beryllium, magnesium, calcium, strontium, barium, and radium belong, from the perspective of high lithium ion conductivity. Among them, the silicate phase is preferably a silicate phase containing lithium (hereinafter sometimes referred to as a lithium silicate phase) from the perspective of high lithium ion conductivity.

[0039] Lithium silicate phase is represented by the formula: Li 2z SiO 2+z (0<z<2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z preferably satisfies the relationship of 0<z<1, and more preferably z=1 / 2.

[0040] Si-based materials, such as SiO x (preferably in the range of 0<x<2, more preferably in the range of 0.5≤x≤1.6). The Si-based material in which Si particles are dispersed in the carbon phase is represented by the general formula Si x C y (preferably in the range of 0<x≤1 and 0<y≤1).

[0041] A conductive layer covered with conductive carbon can be formed on the surface of the Si-based material. The conductive layer can be formed, for example, by a CVD method using acetylene, methane, etc., or by a method of mixing coal tar, petroleum asphalt, phenolic resin, etc. with a silicon-based active material and performing a heat treatment. As a heat treatment device for heat treatment, for example, a hot air furnace, a hot press, a lamp, a mantle heater, a ceramic heater, a rotary furnace, etc. can be used. In addition, a conductive layer can also be formed by fixing a conductive filler such as carbon black to the particle surface of the Si-based material using a bonding material.

[0042] Regarding the negative electrode active material, in addition to carbon materials and Si-based materials, other materials capable of reversibly storing and releasing lithium ions include Sn, alloys containing Sn, Sn-based materials such as tin oxide, and Ti-based materials such as lithium titanate.

[0043] [Spacer]

[0044] Figure 3 : is a schematic cross-sectional view showing an example of a spacer. Figure 3As shown in FIG. 1 , the separator 13 includes a substrate 30 and a functional layer 32 formed on the substrate 30. The functional layer 32 may be provided on one side of the substrate 30 or on both sides of the substrate 30. Here, as long as at least one of the pair of separators 13 used in the electrode body 14 is Figure 3 The spacer shown in the figure may include a substrate 30 and a functional layer 32 formed on the substrate 30. It should be noted that the other of the pair of spacers 13 may be composed of only the substrate 30, for example.

[0045] The substrate 30 is, for example, a porous sheet having ion permeability and insulation, and specifically, may be a microporous film, woven fabric, nonwoven fabric, etc. The material of the substrate 30 is not particularly limited, and may be, for example, polyethylene, polypropylene, polyolefins such as copolymers of polyethylene and α-olefins, acrylic resins, polystyrene, polyester, cellulose, polyimide, polyphenylene sulfide, polyetheretherketone, fluororesin, etc.

[0046] The functional layer 32 includes a heat-resistant layer 34 containing inorganic particles and resin particles 36 dispersed in the heat-resistant layer 34 and having an average particle size (D50) larger than the thickness of the heat-resistant layer 34. The resin particles 36 having an average particle size (D50) larger than the thickness of the heat-resistant layer 34 form protrusions 36a protruding from the surface of the heat-resistant layer 34.

[0047] Examples of the inorganic particles contained in the heat-resistant layer 34 include metal oxide particles, metal nitride particles, metal fluoride particles, and metal carbide particles.

[0048] Examples of metal oxide particles include aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, and manganese oxide. Examples of metal nitride particles include titanium nitride, boron nitride, aluminum nitride, magnesium nitride, and silicon nitride. Examples of metal fluoride particles include aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, and barium fluoride. Examples of metal carbide particles include silicon carbide, boron carbide, titanium carbide, and tungsten carbide.

[0049] The inorganic particles may also be zeolite (M 2 / n O·Al2O3·xSiO2·yH2O, M is a metal element, n is the valence of M, x≥2, y≥0) and other porous aluminosilicates, talc (Mg3Si4O 10 (OH)2) and other layered silicates, barium titanate (BaTiO3), strontium titanate (SrTiO3) and other minerals, etc. It should be noted that these may be used alone or in combination of two or more.

[0050] The average particle size (D50) of the inorganic particles is preferably in the range of 0.1 μm to 1.0 μm, for example. In this specification, D50 means the particle size at which the cumulative frequency in the volume-based particle size distribution reaches 50% from the smaller particle size side, also known as the median diameter. The particle size distribution of the inorganic particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bel Co., Ltd.) using water as a dispersion medium.

[0051] The content of the inorganic particles contained in the heat-resistant layer 34 is, for example, preferably in the range of 15 mass % to 85 mass %, and more preferably in the range of 30 mass % to 60 mass %, relative to the total mass of the heat-resistant layer 34 .

[0052] The thickness of the heat-resistant layer 34 is preferably smaller than the thickness of the base material 30 , and is, for example, 0.5 μm to 5 μm.

[0053] The heat-resistant layer 34 preferably further includes a binder. The binder has the function of bonding the individual inorganic particles to each other and bonding the inorganic particles to the substrate 30. As an example of a binder, fluorine-based resins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide-based resins, acrylic resins, polyolefin-based resins, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyvinyl alcohol (PVA), etc. can be cited. They can be used alone or in combination of two or more. The content of the binder contained in the heat-resistant layer 34 is preferably 0.5 to 10% by mass, and more preferably 1 to 5% by mass, relative to the total mass of the heat-resistant layer 34.

[0054] The resin particles 36 dispersed in the heat-resistant layer 34 need to have an average particle size (D50) larger than the thickness of the heat-resistant layer 34. The average particle size (D50) of the resin particles 36 depends on the thickness of the heat-resistant layer 34, but is preferably in the range of 2 to 10 μm, for example.

[0055] The content of the resin particles 36 dispersed in the heat-resistant layer 34 is preferably in the range of 1 mass % to 15 mass % and more preferably in the range of 3 mass % to 7 mass % relative to the total mass of the heat-resistant layer 34 in order to ensure good adhesion of the spacer 13 .

[0056] Regarding the protrusions 36a formed by the resin particles 36, for example, from the perspective of ensuring good adhesion of the spacer 13, when looking down at the surface of the functional layer 32, preferably there are 10 to 35 protrusions 36a in the range of 100 μm×100 μm, and more preferably there are 15 to 30 protrusions 36a.

[0057] As the resin particles 36, for example, known polymers that can be used as a binder can be used. As monomer units constituting the resin particles 36 (polymers), for example, aromatic vinyl monomer units, (meth)acrylate monomer units, fluorine-containing monomer units, etc. can be cited. It should be noted that in the present application, the so-called "(meth)acrylic acid" means acrylic acid and / or methacrylic acid. It should be noted that the so-called resin particles 36 (polymers) "contain monomer units" means that the polymer obtained using the monomer contains repeating units derived from the monomer.

[0058] Examples of the aromatic vinyl monomer capable of forming the aromatic vinyl monomer unit are not particularly limited, and examples thereof include styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene. Examples of the (meth)acrylate monomers that can form the (meth)acrylate monomer units include butyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, and tert-butyl acrylate; alkyl acrylates such as octyl acrylates such as pentyl acrylate, hexyl acrylate, heptyl acrylate, and 2-ethylhexyl acrylate; nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and butyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate; octyl methacrylates such as pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, and 2-ethylhexyl methacrylate; nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate; and alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate.

[0059] Examples of the fluorine-containing monomer capable of forming the fluorine-containing monomer unit are not particularly limited, and examples thereof include vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, vinyl fluoride, and perfluoroalkyl vinyl ether.

[0060] The resin particles 36 may further include crosslinking monomer units in addition to the above-mentioned monomer units. Here, the so-called crosslinking monomer unit is a monomer that can form a crosslinking structure during or after polymerization by heating or irradiation with energy rays. As a monomer that can form a crosslinking monomer unit, for example, a multifunctional monomer having two or more polymerization reactive groups in the monomer can be cited. As such a multifunctional monomer, for example, divinyl compounds such as allyl methacrylate and divinylbenzene can be cited; di(meth)acrylate compounds such as diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and 1,3-butanediol diacrylate; tri(meth)acrylate compounds such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate, etc.

[0061] The resin particles 36 can be prepared by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. The polymerization method is not particularly limited, and may be, for example, a suspension polymerization method, an emulsion polymerization coagulation method, a pulverization method, etc. In addition, as the polymerization reaction, any reaction such as free radical polymerization and living free radical polymerization can be used.

[0062] The monomer composition used to prepare the resin particles 36 may contain other materials such as a chain transfer agent, a polymerization regulator, a polymerization reaction retarder, a reactive fluidizing agent, a filler, a flame retardant, an anti-aging agent, and a colorant in any amount.

[0063] An example of a method for producing the spacer 13 of the present embodiment is described. For example, inorganic particles, a heat-resistant resin, resin particles 36, water as a dispersion medium, and other components (such as a binder, etc.) used as needed are mixed to prepare a slurry composition for a functional layer. Then, the slurry for a functional layer is applied to a substrate and then dried, thereby producing the spacer 13 of the present embodiment.

[0064] Figure 4 This is a diagram showing the state of the positive electrode, negative electrode, and separator by unfolding the inner end side of the winding direction of the electrode body. Figure 4 As shown in FIG. 1 , the separator 13 constituting the electrode body 14 is arranged so that the functional layer 32 faces the positive electrode 11. Figure 4 As shown, a pair of spacers 13 are bonded to each other at the non-opposing portion 12a of the negative electrode 12, and a large space S1 is formed between the negative electrode 12 and the spacer 13 at the non-opposing portion 12a. By forming such a space S1, it is difficult to retain the non-aqueous electrolyte at the non-opposing portion 12a of the negative electrode 12, so that the decomposition of the non-aqueous electrolyte on the non-opposing portion 12a caused by the charge and discharge of the battery is suppressed, and the reduction in the initial charge and discharge efficiency of the battery is suppressed. Figure 4In the embodiment, the functional layer 32 of each of the pair of separators 13 faces the positive electrode 11 , but it is sufficient that the functional layer 32 of at least one of the pair of separators 13 faces the positive electrode 11 .

[0065] Figure 5 This is a diagram showing the state of the positive electrode, negative electrode, and separator by unfolding the inner end side of the winding direction of the conventional electrode body. Figure 5 As shown in FIG. 1 , the separator 13a constituting the conventional electrode body 14a does not include the functional layer 32 (for example, it is composed of only the substrate 30). Therefore, in the non-opposing portion 12a of the negative electrode 12, the pair of separators 13a are not bonded to each other, and a narrow space S2 is formed between the negative electrode 12 and the separator 13a in the non-opposing portion 12a. Since the non-aqueous electrolyte is easily retained in such a narrow space S2, it is considered that the non-aqueous electrolyte is easily decomposed in the non-opposing portion 12a of the negative electrode 12.

[0066] Example

[0067] Hereinafter, the present application will be further described using examples; however, the present application is not limited to these examples.

[0068] <Example 1>

[0069] [Production of positive electrode]

[0070] 100 parts by mass of LiNi 0.88 Co 0.09 Al 0.03 O2, 1 part by mass of acetylene black (AB) and 0.9 part by mass of polyvinylidene fluoride (PVDF) are mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode mixture slurry. Then, the positive electrode mixture slurry is applied to both sides of an aluminum foil with a thickness of 15 μm, and the coating is dried. Then, after rolling the coating using a roller, it is cut into a specified electrode size to produce a positive electrode with a positive electrode mixture layer formed on both sides of the positive electrode collector. In the central part of the longitudinal direction of the positive electrode, an exposed portion where the positive electrode mixture layer is not formed and the positive electrode collector is exposed is provided, and an aluminum positive electrode lead is welded to the exposed portion.

[0071] [Production of negative electrode]

[0072] 88 parts by mass of graphite powder, 12 parts by mass of Si-based materials, 0.56 parts by mass of carbon nanotubes (CNT), 1 part by mass of sodium carboxymethylcellulose (CMC-Na) and 1 part by mass of styrene butadiene rubber (SBR) dispersion were mixed, and an appropriate amount of water was added to prepare a negative electrode mixture slurry. Then, the negative electrode mixture slurry was applied to both sides of a copper foil with a thickness of 8 μm, and the coating was dried. Then, after rolling the coating using a roller, it was cut into a specified electrode size to produce a negative electrode with a negative electrode mixture layer formed on both sides of the negative electrode collector. At one end of the negative electrode in the longitudinal direction (the inner end in the winding direction of the electrode body), an exposed portion where the negative electrode mixture layer is not formed and the negative electrode collector is exposed is provided, and a nickel negative electrode lead is welded to the exposed portion.

[0073] [Making spacers]

[0074] A porous substrate made of polyethylene with a thickness of 12 μm was prepared. α-Al2O3 powder (inorganic particles) with an average particle size (D50) of 0.8 μm, acrylic resin particles (hereinafter referred to as acrylic resin particles) formed by a copolymer of 2-ethylhexyl acrylate and styrene with an average particle size (D50) of 3 μm, and an acrylic adhesive (binder) were mixed at a solid content mass ratio of 100:6:5, and an appropriate amount of water was added so that the solid content concentration was 10% by mass to prepare a slurry for a functional layer. The slurry for the functional layer was applied to the entire area of ​​one surface of the substrate using a micro-gravure coater, and the coating was heated and dried in an oven at 50°C for 4 hours to obtain a spacer having a functional layer having a heat-resistant layer formed on one surface of the substrate. The surface of the functional layer of the spacer was observed using a scanning electron microscope, and as a result, multiple protrusions of the above-mentioned resin particles protruding from the heat-resistant layer were observed. Multiple protrusions were also observed in other embodiments.

[0075] [Electrode body production]

[0076] After stacking in the order of separator, positive electrode, separator, and negative electrode, the stack is wound into a spiral to produce a wound electrode body. At this time, a pair of separators is arranged so that the functional layers of each pair of separators are opposite to the positive electrode. The number of windings of the electrode body is set to 18 times based on the positive electrode. In addition, the non-opposing portion of the negative electrode is wound 1.5 times from the inner end of the winding direction of the electrode body.

[0077] [Preparation of non-aqueous electrolyte]

[0078] To 100 parts by mass of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7, 5 parts by mass of vinylene carbonate (VC) was added, and lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1.5 mol / L to prepare a non-aqueous electrolyte.

[0079] [Manufacturing of non-aqueous electrolyte secondary batteries]

[0080] Insulating plates were placed above and below the electrode body, and the electrode body was placed in an outer can. The negative electrode lead was welded to the bottom of the outer can with a bottom and the positive electrode lead was welded to the sealing body. After the non-aqueous electrolyte was injected into the outer can, the opening of the outer can was sealed with the sealing body through the liner, and then left to stand in a constant temperature chamber at 60°C for 15 hours to produce a non-aqueous electrolyte secondary battery.

[0081] <Example 2>

[0082] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the acrylic resin particles having an average particle size (D50) of 3 μm were replaced with acrylic resin particles having an average particle size (D50) of 5 μm in the preparation of the separator.

[0083] <Example 3>

[0084] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that the acrylic resin particles having an average particle size (D50) of 3 μm were replaced with acrylic resin particles having an average particle size (D50) of 7 μm in the production of the separator.

[0085] <Example 4>

[0086] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass and the Si-based material was replaced from 12 parts by mass to 6 parts by mass in the production of the negative electrode.

[0087] <Example 5>

[0088] A non-aqueous electrolyte secondary battery was produced using the same method as in Example 1, except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass, the Si-based material was replaced from 12 parts by mass to 6 parts by mass, and the winding of the non-opposing part of the negative electrode was replaced from 1.5 turns to 2.5 turns in the production of the electrode body.

[0089] <Example 6>

[0090] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass, the Si-based material was replaced from 12 parts by mass to 6 parts by mass in the production of the negative electrode, and the acrylic resin particles with an average particle size (D50) of 3 μm were replaced with acrylic resin particles with an average particle size (D50) of 5 μm in the production of the separator.

[0091] <Example 7>

[0092] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass, the Si-based material was replaced from 12 parts by mass to 6 parts by mass in the production of the negative electrode, and the acrylic resin particles with an average particle size (D50) of 3 μm were replaced with acrylic resin particles with an average particle size (D50) of 7 μm in the production of the separator.

[0093] <Example 8>

[0094] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass, the Si-based material was replaced from 12 parts by mass to 6 parts by mass in the production of the negative electrode, and the acrylic resin particles with an average particle size (D50) of 3 μm were replaced with acrylic resin particles with an average particle size (D50) of 10 μm in the production of the separator.

[0095] <Comparative Example 1>

[0096] A non-aqueous electrolyte secondary battery was produced using the same method as in Example 1, except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass, the Si-based material was replaced from 12 parts by mass to 6 parts by mass, and the winding of the non-opposing part of the negative electrode was replaced from 1.5 weeks to 1 week in the production of the electrode body.

[0097] <Comparative Example 2>

[0098] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the graphite powder was replaced from 88 parts by mass to 94 parts by mass, the Si-based material was replaced from 12 parts by mass to 6 parts by mass, and a porous substrate made of polyethylene with a thickness of 12 μm was used as a separator.

[0099] <Comparative Example 3>

[0100] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that a 12 μm thick polyethylene porous substrate was used as a separator.

[0101] [Initial charge and discharge efficiency]

[0102] The non-aqueous electrolyte secondary battery of each embodiment and each comparative example was charged at a constant current of 0.3 It until the battery voltage was 4.2 V, and then charged at a constant voltage of 4.2 V until the current was 0.02 It. Thereafter, it was discharged at a constant current of 1.0 It until the battery voltage was 2.7 V. The charge capacity and discharge capacity at this time were set as the initial charge capacity and the initial discharge capacity, and the initial charge and discharge efficiency was calculated using the following formula.

[0103] Initial charge and discharge efficiency (%) = (initial discharge capacity / initial charge capacity) × 100

[0104] [Evaluation of plate deformation]

[0105] The above-mentioned charge and discharge is set as one cycle, and a 20-minute rest time is inserted between each cycle, and 500 cycles are performed. After 500 cycles, the non-aqueous electrolyte secondary battery is charged at a constant current of 0.3 It until the battery voltage reaches 4.2 V, and then charged at a constant voltage of 4.2 V until the current reaches 0.02 It to set it to a charged state. The non-aqueous electrolyte secondary battery in the charged state is observed using an X-ray CT device (manufactured by Shimadzu Corporation, SMX-225CT FPD HR) to observe the cross-section near the winding center of the electrode body. Figure 6 As shown, when deformation (bending) of the electrode plate (at least one of the positive electrode 11 and the negative electrode 12) was confirmed to be 150 degrees or less, it was determined that the electrode plate was deformed, and the presence or absence of electrode plate deformation was evaluated. The number of batteries evaluated was 3.

[0106] The evaluation results of the initial charge and discharge efficiency and the electrode plate deformation of each embodiment and each comparative example are summarized in Table 1. When all the three batteries evaluated had no electrode plate deformation, the evaluation was 0, and even when one battery was confirmed to have electrode plate deformation, the evaluation was ×.

[0107] [Table 1]

[0108]

[0109] In Examples 1 to 8, the initial charge and discharge efficiency showed a high value of 85% or more, and no plate deformation occurred. On the other hand, in Comparative Example 1, although the initial charge and discharge efficiency showed a high value, the plate deformation occurred. In addition, in Comparative Example 2, although no plate deformation occurred, the initial charge and discharge efficiency was a low value of less than 85%. In Comparative Example 3, the initial charge and discharge efficiency was low, and the plate deformation also occurred.

[0110] Description of Reference Numerals

[0111] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 12a non-opposing portion, 12b opposing portion, 13, 13a separator, 14, 14a electrode body, 15 battery case, 16 outer packaging body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 protrusion, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 substrate, 32 functional layer, 34 heat-resistant layer, 36 resin particles, 36a protrusion.

Claims

1. A non-aqueous electrolyte secondary battery comprising an electrode body obtained by winding a positive electrode and a negative electrode with a pair of separators interposed therebetween, and a non-aqueous electrolyte, The negative electrode has a non-opposing portion that is opposed to the positive electrode via the pair of separators, and the non-opposing portion is wound 1.5 turns or more from the inner end in the winding direction of the electrode body. At least one of the pair of spacers includes a base layer and a functional layer formed on the base layer. The functional layer includes a heat-resistant layer containing inorganic particles, and resin particles dispersed in the heat-resistant layer and having an average particle diameter larger than a thickness of the heat-resistant layer. The resin particles form convex portions protruding from the surface of the heat-resistant layer, The functional layer of at least one of the pair of separators faces the positive electrode.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein: The average particle size of the resin particles is in the range of 2 μm to 10 μm.

3. The non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode comprises a negative electrode current collector and a negative electrode mixture layer disposed on the negative electrode current collector. The negative electrode mixture layer comprises Si-based materials and carbon materials, The Si-based material includes a lithium ion conductive phase and Si particles dispersed in the lithium ion conductive phase.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2013137946A